The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10592-005-4988-9
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of nuclear and mitochondrial DNA variation among South American Burmeister’s porpoises (Phocoena spinipinnis)

Abstract: Little is known about the biology of Burmeister's porpoises (Phocoena spinipinnis), a small cetacean species endemic to South American waters. Information on stock structure, however, is urgently needed, as the species suffers from considerable mortality due to local fishery activities throughout its distribution range. Using mitochondrial control region sequences and 11 species-specific microsatellite loci, we assessed the genetic differentiation among 118 stranded, incidentally or directly-caught Burmeister'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 37 publications
(34 reference statements)
5
67
0
1
Order By: Relevance
“…The Bahia Samborombon, to the north of San Clemente, is an enclosed habitat with shallow waters and high prey abundance (Bezzi and Boschi 2000;Lasta 1995;Lasta and Acha 1996), which would make it suitable for calving. Our hypothesis is supported by other case studies involving two small cetacean species in which ecological features seem to play important roles in maintaining population differentiation Rosa et al 2005).…”
Section: Isolation By Distance?supporting
confidence: 85%
See 1 more Smart Citation
“…The Bahia Samborombon, to the north of San Clemente, is an enclosed habitat with shallow waters and high prey abundance (Bezzi and Boschi 2000;Lasta 1995;Lasta and Acha 1996), which would make it suitable for calving. Our hypothesis is supported by other case studies involving two small cetacean species in which ecological features seem to play important roles in maintaining population differentiation Rosa et al 2005).…”
Section: Isolation By Distance?supporting
confidence: 85%
“…This is not an unusual finding in coastally distributed small cetaceans (Natoli et al 2005;Rosa et al 2005;Sellas et al 2005), although cases of male-biased dispersal are more frequently reported (Adams and Rosel 2006;Cassens et al 2005;Escorza Treviño and Dizon 2000;Moller and Beheregaray 2004;Rosel et al 1995Rosel et al , 1999. It has been suggested that mtDNA can be used to infer patterns of differential migration between sexes by identifying cases of significant female genetic structure (Escorza Treviño and Dizon 2000).…”
Section: Sex-biased Dispersalmentioning
confidence: 95%
“…Although the Mozambique and Tanzania samples are relatively small, the samples used in this analysis are the only ones that exist for the study area and can therefore provide relevant population structure information. Moreover, these sample sizes are comparable to those used in other population genetic studies in cetaceans (Dalebout et al, 2001;Chivers et al, 2002;Rosa et al, 2005;Mendez et al, 2010).…”
Section: Methodssupporting
confidence: 64%
“…Therefore, genetic distances between contiguous populations have the greatest biological relevance. In this context, the magnitude of the genetic structure observed between populations in Oman and Tanzania (F ST B0.34, F ST B0.64), or those in Tanzania and Mozambique (F ST B0.46, F ST B0.69), is statistically and biologically meaningful and much higher, for example, than that of neighboring populations of other small cetaceans in coastal South America (Rosa et al, 2005;Mendez et al, 2008Mendez et al, , 2010. The combined genetic evidence from the fixation indices, migration rates and divergence times suggests that although the Oman and Tanzania populations diverged before all other populations, they are currently not the most isolated.…”
Section: Population Structurementioning
confidence: 97%
“…Milinkovitch et al 2002), these data are never-the-less essential to the identification and conservation of diversity, and various factors have been shown to be relevant to the evolution of structure in these species. For example, historical processes, in particular the Pleistocene glaciations in the Northern Hemisphere, have been proposed as an important factor leading to genetic differentiation among marine species and populations, promoting speciation and influencing the distribution of lineages in coastal areas (e.g., Reeb and Avise 1990;Hewitt 2000;Hayano et al 2004;Rosa et al 2005;Adams et al 2006;Haney et al 2007). It has been hypothesized that during these climatic changes the distribution ranges of many marine species were restricted due to the creation of physical barriers (e.g., changes in sea level and sea temperatures) that reduced gene flow, even among proximate populations, and increased the effect of evolutionary forces such as genetic drift and selection (Avise et al 1998;Hewitt 1996Hewitt , 2000Haney et al 2007).…”
Section: Introductionmentioning
confidence: 99%